Perspektif Dr. Ali Al-Qasmy pada Kamus Akbar Bahasa Arab (Indonesia-Arab) - Siti Ghitsna Naily Nasyithoh; Siti Masrifah Nur Aini; Thayyib Thayyib; Mokhammad Miftahul Huda (Jurusan Pendidikan Bahasa Arab, 2021)
The ideal dictionary is one that meets the components that have been established by the researchers. The research of akbar dictionary aims to observe and analyze the completeness of components according to the perspective of Dr. Ali Al-Qasimy in akbar Arabic (Indonesian-Arabic) dictionary. In this study, researchers used library research methods with a discriptive method. Obtaining data from akbar Arabic (Indonesian-Arabic) dictionary by tracing the source of literature and documentation techniques. The result of this research of Akbar Bahasa Arab (Indonesia-Arabic) dictionary is that this dictionary is almost perfect in its preparation and meets 24 components of 27 components that have been delivered by Dr. Ali Al-Qasimy. Therefore, researchers argue that this dictionary is an ideal dictionary that deserves to be used as a reference by various circles and especially for the academic community and translators and Arabic learners.